To the Right Honourable John Lord Sommers, Baron of Evesham in [th]e County of Worcester, President of Her Majesty's most Honourable Privy Council &c., this map of North America according to [th]e newest and most exact observations is most humbly dedicated by your Lordships most humble servant Herman Moll, geographer - Moll, Herman, d. 1732 ([London])
Hand coloured. Compass rose. Prime meridian London. Decorative title cartouche. Shows prevailing winds. Relief shown pictorially. "B. Lens delin., G. Vertue sculp." (title cartouche). Includes notes. -- Illustration: "A view of a stage & also of [th]e manner of fishing for, curing & drying cod at New Found Land ." Includes legend. -- Insets, each with north arrow and bar scale: St. John's harbour -- Boston harbour -- New York -- Ashley & Cooper River -- Port Royal harbour -- The bay & city of [th]e Havana -- The bay of Pto. Bella -- La Vera Cruz -- Cartagena harbour and forts -- The port of Acapulco. "Printed for H. Moll. D. Midwinter at [th]e 3 Crowns in St. Pauls Church yard and T. Bowles Print and Mapseller next to the Chapter house in St. Pauls Church yard, and over against Devereux Court, without Temple Bar. And by P. Overton Map and Printseller near St. Dunftans Church Fleetstreet" (top edge center).